บทบาทของพระสงฆ์ในศตวรรษที่ 21 - ดร., พระครูสุธีจริยวัฒน์, (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2019)
The key success factors of promoting the sustainable prosperity of Buddhism. The priest is responsible for promoting the preservation of Buddhist teachings and propagation of a role model. The Buddhists Strengthen and stabilize the Buddhism in the 21st century has changed in many ways. Priests need to be adjusted to suit the situation has changed, but still preserves the original target. The role of the clergy needed to improve. The essential applied roles of Buddhist executive monks include a role in Buddhist missionaries, a symbolic role in Buddhism, a magician role, a faith management role, a spiritual leader role, a social developer role and a misery eradicator role. Hopefully, the achievement in taking such roles will help preserve and enhance Buddhism to last forever.  Keywords : Roles, Buddhist Monks. 21 st Century